(untitled) (Academicia Globe: Inderscience Research, 2022)
The scientific work of scientists in improving the efficiency of management of industrial enterprises has been theoretically studied. In describing the development processes of management of industrial enterprises, the real object is presented in the form of two systems, namely, managerial and managed.